Remittances and migration intentions of the left-behind. (2nd January 2017) - Piracha, Matloob; Saraogi, Amrita
Abstract : Migration and the consequent flow of remittances are like a double-edged sword; while keeping many out of poverty, they can also result in further brain drain and demographic imbalance for the country. Using a large household survey data from Moldova and employing simultaneous equations model we show that there exists a dual causality between receipt of remittances by non-migrants and their migration intentions. Moreover, we add a novel element to the empirical literature by specifying the mechanism behind the link between remittances and migration. We find evidence that remittances not only relieve credit constraints in the home country but also act as a signalling device of success in the host country. These results provide a fresh outlook on the role of remittances in shaping migration flows in the migrant sending countries.